2018
DOI: 10.1080/13511610.2017.1419337
|View full text |Cite
|
Sign up to set email alerts
|

International comparative explorations of prostitution policies: lessons from two European projects

Abstract: In this contribution we reflect on our experiences of co-designing and coordinating two comparative projects on prostitution policies in Europe by focusing in particular on the epistemological workings underpinning their design and execution. We set out two main goals. The first is to shed light on what the epistemological and methodological issues we encountered reveal about the field of prostitution policy studies, an endeavour which can contribute to better comparative research in the field. The second goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…To provide a detailed account of the policy development in these countries is outside the scope of this paper (for thorough account see: Crowhurst & Skilbrei, 2018;Wagenaar & Jahnsen, 2018). Instead, I present only major changes in prostitution policy from 1990s and onward for these eight countries to test the hypothesis on prostitution law and sex-buying behaviour.…”
Section: Legal Context In the Different Countriesmentioning
confidence: 99%
“…To provide a detailed account of the policy development in these countries is outside the scope of this paper (for thorough account see: Crowhurst & Skilbrei, 2018;Wagenaar & Jahnsen, 2018). Instead, I present only major changes in prostitution policy from 1990s and onward for these eight countries to test the hypothesis on prostitution law and sex-buying behaviour.…”
Section: Legal Context In the Different Countriesmentioning
confidence: 99%
“…Existing research has shown considerable global interest in the model. Many scholars conclude that the 'Swedish' or 'Nordic' model is among the international prostitution policies most often discussed and debated (Ward and Wylie, 2017;Crowhurst and Skilbrei, 2018;McMenzie et al, 2019). Moreover, the dominance of the 'Nordic' adjective suggests that this label may be more than a geographic and descriptive signifier model.…”
Section: Importing the Nordic Modelmentioning
confidence: 99%
“…Indeed, the switch by campaigners from the term 'Swedish model' to the 'Nordic model' more firmly placed the model in the realm of gender equality and social welfarism. 13 In the case of prostitution policy circulation, researchers (Crowhurst and Skilbrei, 2018) have demonstrated that there is a particularly lively transnational exchange and a strong idea that prostitution is an area where policies would benefit from being harmonized. As demonstrated above, 'the Nordic model' can be put to use for securing agendas that are already present in domestic contexts but can be rebranded and legitimized as an uptake of Nordicity.…”
Section: Conclusion: Explaining Mobilitymentioning
confidence: 99%
“…The use of various approaches to the regulation of prostitutional relations in European countries sets the task of finding the optimal model that can resolve the contradictions associated with the existence of prostitution. So, at the European level, the question was raised about determining the most effective form of regulation of prostitutional relations, harmonization of legal norms and the exchange of best management practices in different jurisdictions (Crowhurst & Skilbrei, 2018). In Russia, they currently adhere to a criminalization policy.…”
Section: Introductionmentioning
confidence: 99%